Bioactive compounds (phytoestrogens) recovery from Larrea tridentata leaves by solvents extraction - Martins, Silvia (2012)
Methanol, ethanol, and acetone at four different concentrations (90%, 70%, 50%, and 30% v/v) were used for extraction of phytoestrogens (nordihydroguaiaretic acid (NDGA), kaempferol, and quercetin) from Larrea tridentata leaves. Besides the phytoestrogens extraction, the antioxidant potential, and the contents of total phenols, flavonoids, and protein in the produced extracts were also determined. The solvent and concentration used for extraction strongly affected the phytoestrogens recovery. The highest NDGA, quercetin, and kaempferol contents (46.96 ± 3.39, 10.46 ± 1.01, and 87.00 ± 6.43 mg/g DW plant, respectively) were recovered using 90% (v/v) methanol. All the produced extracts showed antioxidant capacity, but those obtained using 70% and 90% (v/v) methanol had significantly higher (p < 0.05) FRAP (ferric reducing antioxidant power) values (2.55 ± 0.09 and 2.73 ± 0.11 mM FE(II)/g DW plant, respectively) than the remaining ones. Extract produced by using 90% (v/v) methanol contained also the highest contents of total flavonoids (19.29 ± 0.79 mg QE/g DW plant) and protein (131.84 ± 6.23 mg/g DW plant), and elevated total phenols concentration (263.60 ± 25.78 mg GAE/g DW plant).